Pengembangan Aplikasi Kontrol Kendali Kemudi Kursi Roda Berbasis Pergerakan Kepala HEMOCS (Head Movement Control System) - Muhammad Ridho Kurniawan Pratama; Herman Tolle; Mahardeka Tri Ananta (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Head Movement Control System (HEMOCS) is a control method which utilizing head movement, especially for mobile device interaction. Wheelchair Control Application Based On HEMOCS developed so the wheelchair movement can be controlled independently by someone who can't use their hands with help from Bluetooth Low Energy connectivity as data communication media between application and wheelchair. Head movement such as up, down, left, right, tilt left, and tilt right head movement can be recognized appropriately. Wheelchair movement will be controlled using those head movements. Head movement that has been conducted during accuracy testing with duration 0,4 until 0,6 seconds, with average angle 22,63 degrees, and with duration 0,7 until 0,9 seconds, with average angle 27,21 degrees can be recognized accurately with 100% procentage.